USAHA KECIL MENENGAH (UKM) SEBAGAI SOLUSI PERTUMBUHAN EKONOMI DAERAH LABUHANBATU - Siregar, Marlina (Universitas Labuhanbatu, 2021)
Economic growth is one form of physical development that occurs in goods and services that are currently in effect in a country. Development in an area is one form of the concept and purpose of national development, the developments that are mostly carried out in the regions are one form that can show that Indonesia has moved to a more advanced level. One of the factors that can affect economic growth in Labuhan Batu is Small and Medium Enterprises (UKM), which is one of the business activities that have very wide business opportunities, because Small and Medium Enterprises (SMEs) are engaged in all economic sectors, both agricultural and non-agricultural. This research uses literature study method. Based on data obtained from the Central Statistics Agency in Labuhanbatu district, the growth of Small and Medium Enterprises (SMEs) is very influential on economic growth in Labuhanbatu district. The results of respondents who are Small and Medium Enterprises stated that the existence of Small and Medium Enterprises (SMEs) and the provision of training to them can help their economy. thanks to the knowledge given they can manage the business even better. Then with various trainings they can be more creative and can develop their business ideas. because at this time the selling value is not seen from the product or raw materials only.